Transjugular Intrahepatic Portosystemic Shunts in Patients with Hepatic Malignancy - Wallace, Michael J. (Thieme Medical Publishers, 2005)
Since its first clinical application in 1988, the transjugular intrahepatic portosystemic shunt (TIPS) has emerged as a safe and effective means of managing patients with morbid portal hypertension. Despite the considerable body of literature on TIPS, portal decompression in patients with malignancy has not been sufficiently examined. These patients typically experience sequelae of portal hypertension that requires palliation. The purpose of this article is to review the reported experience with TIPS in patients with malignancy.